ETHICAL COMMITMENT IN CHOOSING MEDICAL REPRESENTATIVE PROFESSION: A STUDY ON STUDENTS OF MEDICAL PROMOTION AND MARKETING (Third Sector Social Economic Review, 2018)
The purpose of this study is to find out the reason why the graduates of Medical Promotion and Marketing are not volunteer to do their own jobs claiming that this job is not appropriate for them in terms of their moral and religious values. Method; For this purpose, a suitable vocational attitude scale has been conducted on 204 students studying this department at Karabük University in April, 2016. Besides fivefold vocational attitude scale, the students were asked demographic information and osgood types of questions to reveal the correlation between them. Conclision; The question about the level of belief and medical promotion reveals that pearson correlation is p=0,036.
Keywords: Ethics; Medical Representative; Marketing of Health Services; Ethic Values; Vocational Attitude